The Admonition of god to prophet Muhammad SAW ('Itab) in the Qur'an and its impact to the concept of Ijtihad and 'Ismah - Abdul Haris Nasution (Fak. Ushuluddin dan Pemikiran Islam UIN Sunan Kalijaga, 2015)
irh,1/ws.c.1